II. Dissociation free energies in drug–receptor systems via nonequilibrium alchemical simulations: application to the FK506-related immunophilin ligands. Issue 22 (19th May 2016) - Nerattini, Francesca; Chelli, Riccardo; Procacci, Piero
Abstract : The fast switch double annihilation method (FS-DAM) provides an effective mean to the compute the binding free energies in drug-receptor systems. Here we present an application to the FK506-related ligands of the FKBP12 protein. Abstract : The recently proposed fast switching double annihilation (FS-DAM) [Cardelli et al., J. Chem. Theory Comput., 2015, 11, 423] is aimed at computing the absolute standard dissociation free energies for the chemical equilibrium RL ⇌ R + L occurring in solution through molecular dynamics (MD) simulations at the atomistic level. The technique is based on the production of fast nonequilibrium annihilation trajectories of one of the species (the ligand) in the solvated RL complex and in the bulk solvent. As detailed in the companion theoretical paper, the free energies of these two nonequilibrium annihilation processes are recovered by using an unbiased unidirectional estimate derived from the Crooks theorem exploiting the inherent Gaussian nature of the annihilation work. The FS-DAM technique was successfully applied to the evaluation of the dissociation free energy of the complexes of Zn(ii ) cations with an inhibitor of the Tumor Necrosis Factor α converting enzyme. Here we apply the technique to a real drug–receptor system, by satisfactorily reproducing the experimental dissociation free energies of FK506-related bulky ligands towards the native FKBP12 enzyme and by predicting the dissociation constants for the same ligands towards the mutant I56D. The effect of such mutations on the binding affinity of FK506-related ligands is relevant for assessing the thermodynamic forces regulating molecular recognition in FKBP12 inhibition.